Risk factors for childhood drowning in rural regions of a developing country: a case–control study. Issue 3 (13th June 2007) - Yang, Li; Nong, Quan-Qing; Li, Chun-Ling; Feng, Qi-Ming; Lo, Sing Kai
Abstract : Background: Descriptive epidemiological studies have shown that childhood drowning rates are higher in developing countries, with an increasing trend in rural areas. Aim: To examine risk factors associated with childhood drowning in rural China. Methods: Participants included parents of all children aged 1–14 years who died of drowning between 2002 and 2004 in 20 districts in GuangXi Province, and two age- and gender-matched controls each. Behavioral characteristics of the child and the children's caregivers were collected using a questionnaire and analyzed using logistic regression. Results: Boys (60%) and children aged 1–4 years (48%) were over-represented among the cases; 62% occurred within 500 m of the school or home. Protective fencing or warning signs were found at only two sites. None of the children's caregivers knew how to perform cardiopulmonary resuscitation. For children aged 1–4 years significant risk factors included poor health of the caregiver (OR 3.1; 95% CI 1.9 to 5.8), not using flotation devices (OR 2.3; 95% CI 1.4 to 4.5) and no proper swimming lessons (OR 1.8; 95% CI 1.1 to 5.5). For children aged 5–14 years, the main risk factors were that the child did not have the experience of playing near or in water regularly (OR 2.7; 95% CI 1.8 to 7.4) and lack of close supervision (OR 1.9; 95% CI 1.3 to 5.6). Conclusion: Risk factors identified in this study suggest that childhood drowning in rural areas in developing countries could be prevented by providing safety educational programs, which should focus on constant adult supervision and the use of flotation devices when children play in and near water.